Continuous generalization of water system elements - Yue Chen; Haizhong Qian; Zhihe Fu (Geocarto International)
Continuous generalization effectively tackling the challenge of representing maps at continuous scales. Current research on continuous generalization focuses solely on the continuous simplification of individual element, lacking the capability to handle multiple generalization operators and complex corresponding relationship elements simultaneously. Furthermore, there is limited research on the continuous collapse, and existing methods have failed to fully consider the curved structures of polygon elements. Therefore, this study proposed a novel continuous generalization method for water system elements. Firstly, the two scale map elements are matched. According to different matching conditions, continuous simplification, collapse, and deletion of elements are studied based on Morphing. This study extracted the skeleton line of surface elements to use as a bridge, establishing the corresponding relationship between surface elements and line elements to complete the continuous collapse. Experimental results showed that the proposed method can produce reasonable and smooth continuous morphing effects for multi-elements and multi-operators.